A novel enzyme entrapment in SU-8 microfabricated films for glucose micro-biosensors - Psoma, Sotiria D.; van der Wal, Peter D.; Frey, Olivier; de Rooij, Nicolaas F.; Turner, Anthony P. F. (Elsevier, 2010)
The present work investigates the utilisation of the widely used SU-8 photoresist as an immobilisation matrix for glucose oxidase (GOx) for the development of glucose micro-biosensors. The strong advantage of the proposed approach is the simultaneous enzyme entrapment during the microfabrication process within a single step, which is of high importance for the simplification of the BioMEMS procedures. Successful encapsulation of the enzyme GOx in “customised” SU-8 microfabricated structures was achieved through optimisation of the one-step microfabrication process. Although the process involved contact with organic solvents, UV-light exposure, heating for pre- and post-bake and enzyme entrapment in a hard and rigid epoxy resin matrix, the enzyme retained its activity after encapsulation in SU-8. Measurements of the immobilised enzyme's activity inside the SU-8 matrix were carried out using amperometric detection of hydrogen peroxide in a 3-electrode setup. Films without enzyme showed negligible variation in current upon the addition of glucose, as opposed to films with encapsulated enzyme which showed a very clear increase in current. Experiments using films of increased thickness or enzyme concentration, showed a higher response, thus proving that the enzyme remained active not only on the film's surface, but also inside the matrix as well. The proposed enzyme immobilisation in SU-8 films opens up new possibilities for combining BioMEMS with biosensors and organic electronics.
Keywords: SU-8 films; Biosensor; Microfabrication; Immobilisation; Glucose oxidase entrapment; BioMEMS